ILLOCUTIONARY SPEECH ACTS IN SONG LYRICS: A PRAGMATICS STUDY ON “KUPU-KUPU” BY TIARA ANDINI - Muhamad Saiful Mukminin (Universitas Pendidikan Muhammadiyah Sorong, 2024)
The present research aims to analyze illocutionary speech acts found within the lyrics of the song Kupu-kupu by Tiara Andini from a pragmatic perspective. The analysis of illocutionary speech acts is based on Searle's taxonomy (1969), which categorizes illocutionary acts into five types: assertive, directive, expressive, commissive, and declarative. The study employs a descriptive qualitative method with a pragmatic approach. Data were collected through listening and note-taking techniques, followed by transcription. Data analysis followed an interactive model including data collection, data reduction, data presentation, and conclusion drawing. The findings indicate the presence of four types of illocutionary speech acts in the lyrics of Kupu-kupu, i.e. directive, assertive, commissive, and expressive. Directive speech acts manifest as instructions or commands to the listener, while assertive speech acts involve statements of truth or fact. On the other hand, commissive speech acts reflect intentions or commitments to future actions, whereas expressive speech acts convey feelings or emotions from the singer or narrator of the song. This research implies how song lyrics can encompass various illocutionary speech acts that influence how listeners interpret the conveyed messages.